2016
DOI: 10.1109/tbcas.2016.2543686
|View full text |Cite
|
Sign up to set email alerts
|

Body-Earth Mover’s Distance: A Matching-Based Approach for Sleep Posture Recognition

Abstract: Sleep posture is a key component in sleep quality assessment and pressure ulcer prevention. Currently, body pressure analysis has been a popular method for sleep posture recognition. In this paper, a matching-based approach, Body-Earth Mover's Distance (BEMD), for sleep posture recognition is proposed. BEMD treats pressure images as weighted 2D shapes, and combines EMD and Euclidean distance for similarity measure. Compared with existing work, sleep posture recognition is achieved with posture similarity rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The articles that were included in our analysis were published between 2007 and 2020 and were undertaken in the United States [25][26][27][28][29][30][31][32][33][34][35], China [36][37][38][39][40][41][42][43][44], Spain [45][46][47][48][49][50], Japan [51,52], Italy [53,54], Korea [55], and Greece [56]. According to the applied area of the included studies, we divided the articles into three components: predictive model (12 studies), posture recognition (11 studies), and image analysis (9 studies).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The articles that were included in our analysis were published between 2007 and 2020 and were undertaken in the United States [25][26][27][28][29][30][31][32][33][34][35], China [36][37][38][39][40][41][42][43][44], Spain [45][46][47][48][49][50], Japan [51,52], Italy [53,54], Korea [55], and Greece [56]. According to the applied area of the included studies, we divided the articles into three components: predictive model (12 studies), posture recognition (11 studies), and image analysis (9 studies).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Meanwhile, the classification performance of using DTW-distance-mapping features has been proved to be better than that using DTW as template matching. In addition, the time-consumption complexity of our proposed DTW is O(N 2 ), while that of EMD algorithm is cubic, specifically O(N 3 log n) [53].…”
Section: Discussionmentioning
confidence: 99%
“…21 In 2016, Xu et al identified sleep posture through pressure-sensitive sensor sheets, using the moving distance to use the pressure-sensitive image as a weighted 2D image, combined with earth mover's distance and Euclidean metric for similarity measurement, and experimentally demonstrated that the model improved accuracy by 8.01% compared with traditional sleep posture recognition methods. 22 In 2017, Vecchio et al, by giving the experimenter a device to calculate distance between the experimenter and the gyroscope is used to infer the postural changes of the human body, and the data are classified according to the ultra-wideband transceiver with two-way ranging mode combined with an accelerometer and gyroscope data, but this has certain requirements for the stature of the experimenter, and the accuracy is significantly lower in the case of extreme stature of the subject. 23 Lin et al designed a smart insole that recognizes the activities of the patient for the nursing field, and calculated the temporal and spatial distance based on the built-in pressure sensor, quantifying motion similarity and classifying human posture, and experimental results showed that the classification accuracy for eight common activities in nursing rooms was 91.7%.…”
Section: Sensor-based Gesture Recognitionmentioning
confidence: 99%
“…Sazonov's team used wearable sensors to build an SVM‐based framework for SVM and polynomial logic recognition, and used the labeled data for PAC/EE algorithm training, using fast artificial neural networks (FANNs) to train the MLDs model, the model has been experimentally demonstrated to be effective in reducing execution time for real‐time biofeedback systems 21 . In 2016, Xu et al identified sleep posture through pressure‐sensitive sensor sheets, using the moving distance to use the pressure‐sensitive image as a weighted 2D image, combined with earth mover's distance and Euclidean metric for similarity measurement, and experimentally demonstrated that the model improved accuracy by 8.01% compared with traditional sleep posture recognition methods 22 . In 2017, Vecchio et al, by giving the experimenter a device to calculate distance between the experimenter and the gyroscope is used to infer the postural changes of the human body, and the data are classified according to the ultra‐wideband transceiver with two‐way ranging mode combined with an accelerometer and gyroscope data, but this has certain requirements for the stature of the experimenter, and the accuracy is significantly lower in the case of extreme stature of the subject 23 .…”
Section: Related Workmentioning
confidence: 99%